1985
DOI: 10.1007/bf00119287
|View full text |Cite
|
Sign up to set email alerts
|

Value dimensions in american counseling: A Taiwanese-American comparison

Abstract: This paper is a discussion of prevailing American value dimensions in counseling theory and practice in general and a comparison of Taiwanese-Chinese and American counseling value dimensions in particular. Whereas most studies on cross-cultural issues to date have focused on American majority-minority value conflicts, this paper discusses a new level of value conflict, that between cultures, between nations.Part I discusses differences in cognition and affect between American and Taiwanese-Chinese. We have fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Such clashes in culture have been explored on a larger scale by those such as Hofstede (2001) who suggested that we might consider 'intercultural management' in terms of individualism versus collectivism (which could include competitiveness versus caring), high and low respect for authority, masculinity versus femininity, and short-term versus long-term orientation. Lichia and Raymond (1985) and Lago (2006), amongst others, have used Hofstede's framework to explore value dimensions and issues of race and intercultural counselling; but would such concepts also be helpful in exploring the appropriateness of a therapeutic culture for the communities it serves? The place taken up by teachers and therapists might also be considered abusive in terms of the teachers'/therapists' personal power because of their compliance to the dominant discourse.…”
Section: Resultsmentioning
confidence: 99%
“…Such clashes in culture have been explored on a larger scale by those such as Hofstede (2001) who suggested that we might consider 'intercultural management' in terms of individualism versus collectivism (which could include competitiveness versus caring), high and low respect for authority, masculinity versus femininity, and short-term versus long-term orientation. Lichia and Raymond (1985) and Lago (2006), amongst others, have used Hofstede's framework to explore value dimensions and issues of race and intercultural counselling; but would such concepts also be helpful in exploring the appropriateness of a therapeutic culture for the communities it serves? The place taken up by teachers and therapists might also be considered abusive in terms of the teachers'/therapists' personal power because of their compliance to the dominant discourse.…”
Section: Resultsmentioning
confidence: 99%
“…Jun’s silence needed to be understood in this context. Consistent with Chinese values related to power and dependable authority figures (Lichia & Raymond, 1985), Jun needed scientific answers and appraisals more than discussions about psychological well-being.…”
Section: Making Mental Models Explicit: Discussion Of the Two Casesmentioning
confidence: 96%
“…It is through reflexive awareness that practitioner values and the subsequent influence on clinical decision-making can be brought to the forefront (Adshead, 2009; Fulford, Caroll, & Peile, 2011). Jun’s case highlighted conflicting cultural values, norms, and idioms of distress common to psychiatric practice (Kirmayer, 1989; Lichia & Raymond, 1985). Our approach was congruent with western beliefs about helping, which emphasize individual identity and pharmacological treatment (Kirmayer, 1989; Lichia & Raymond, 1985) unlike Chinese approaches that value collective identity, holistic health and indigenous methods of healing (Kirmayer, 1989; Lichia & Raymond, 1985; Chen & Wong, 2009).…”
Section: Making Mental Models Explicit: Discussion Of the Two Casesmentioning
confidence: 99%
See 1 more Smart Citation